Traditional Cryptocurrencies And Fiat-Backed Digital Currencies - SERGHEI MĂRGULESCU; ELENA MĂRGULESCU (Global Economic Observer)
The digital payments space saw vigorous investment activity during 2020 and there have been a plethora of announcements about account based Central Bank Digital Currencies. The cryptocurrency market can be roughly divided into two segments: traditional cryptocurrencies and fiat-backed digital currencies, including stablecoins and central bank digital currencies. 2021 may be the year we see the world’s first sovereign digital currency. China’s digital yuan or DCEP (short for Digital Currency/Electronic Payments) looks to be nearing completion. DCEP allows China to push forward into the digital era, while still retaining control over its financial instruments. The European Commission and European Central Bank are working together to investigate the policy, legal and technical questions emerging from a possible introduction of a digital euro. But creating a digital currency is actually the easy part. What is more important is how it is linked into the wider ecosystem to ensure the circulation of money and cash flows. Digital currencies are likely to have big implications for the role of central banks and retail lenders and could change the face of the entire financial system.